Nocturnal melatonin increases glucose uptake via insulin-independent action in the goldfish brain - Watanabe, Kazuki; Nakano, Masaki; Maruyama, Yusuke; Hirayama, Jun; Suzuki, Nobuo; Hattori, Atsuhiko (Frontiers in Endocrinology, 2023)
Melatonin, a neurohormone nocturnally produced by the pineal gland, is known to regulate the circadian rhythm. It has been recently reported that variants of melatonin receptors are associated with an increased risk of hyperglycemia and type 2 diabetes, suggesting that melatonin may be involved in the regulation of glucose homeostasis. Insulin is a key hormone that regulates circulating glucose levels and cellular metabolism after food intake in many tissues, including the brain. Although cells actively uptake glucose even during sleep and without food, little is known regarding the physiological effects of nocturnal melatonin on glucose homeostasis. Therefore, we presume the involvement of melatonin in the diurnal rhythm of glucose metabolism, independent of insulin action after food intake. In the present study, goldfish (Carassius auratus) was used as an animal model, since this species has no insulin-dependent glucose transporter type 4 (GLUT4). We found that in fasted individuals, plasma melatonin levels were significantly higher and insulin levels were significantly lower during the night. Furthermore, glucose uptake in the brain, liver, and muscle tissues also significantly increased at night. After intraperitoneal administration of melatonin, glucose uptake by the brain and liver showed significantly greater increases than in the control group. The administration of melatonin also significantly decreased plasma glucose levels in hyperglycemic goldfish, but failed to alter insulin mRNA expression in Brockmann body and plasma insulin levels. Using an insulin-free medium, we demonstrated that melatonin treatment increased glucose uptake in a dose-dependent manner in primary cell cultures of goldfish brain and liver cells. Moreover, the addition of a melatonin receptor antagonist decreased glucose uptake in hepatocytes, but not in brain cells. Next, treatment with N1-acetyl-5-methoxykynuramine (AMK), a melatonin metabolite in the brain, directly increased glucose uptake in cultured brain cells. Taken together, these findings suggest that melatonin is a possible circadian regulator of glucose homeostasis, whereas insulin acquires its effect on glucose metabolism following food intake.